The effect of Traditional Chinese medicine nursing interventions on sleep quality and gastrointestinal function in patients with sepsis (中医特色护理改善脓毒症患者睡眠质量及胃肠功能的效果研究) - LIU Yunlian (刘云莲); NING Hong (宁虹); ZHANG Xiaodan (张晓丹) (Journal of International Translational Medicine Limited, 2024)
Objective To investigate the effect of Traditional Chinese Medicine nursing interventions on sleep quality and gastrointestinal function in patients with sepsis. Methods Totally 84 patients with sepsis accompanied with gastrointestinal function disorder were randomly divided into the control group and observation group, with 42 cases in each group. The conventional nursing mode was adopted in the control group, while the Traditional Chinese medicine nursing interventions including dietary nursing by syndrome differentiation, acupoint massage, Chinese herbal medicine foot bath and hot compress were carried out in the observation group. Acute Physiological and Chronic Health Score (APACHE II) score, Pittsburgh Sleep Quality Index (PSQI) score, improvement in gastrointestinal function, general comfort questionnaire scale (GCQ) score and satisfaction were compared between the two groups. Results Scores of PSQI and APACHE II in the observation group were lower than those in the control group(P＜0. 01). The recovery rate of the observation group was 80. 95%(34/42), which was higher than 64. 29%(27/42)of the control group(P＜0. 05). The GCQ score and patient satisfaction rate in the observation group were higher than those in the control group (P＜0. 05). Conclusion Acupoint massage combined with Traditional Chinese medicine interventions nursing are effective to improve the sleep quality and gastrointestinal function of patients with sepsis. (目的 观察中医特色护理改善脓毒症患者睡眠质量及胃肠功能的效果。方法 选取重症医学科脓毒症胃肠功能障碍患者84例, 随机分为对照组和观察组, 各42例。对照组采用常规护理模式, 观察组采用辨证施膳、穴位按摩、中药足浴、中药热敷等中医特色护理干预。比较两组患者的急性生理与慢性健康评分(APACHE Ⅱ)评分、匹兹堡睡眠质量指数(PSQI)评分, 胃肠功能改善情况、舒适状况量表(GCQ)评分和满意度。结果 观察组患者PSQI和APACHE Ⅱ评分均低于对照组, 差异有统计学意义(P＜0. 01)。干预后, 观察组胃肠功能改善率80. 95%(34/42), 高于对照组的64. 29%(27/42), 差异有统计学意义(P＜0. 05)。观察组患者GCQ量表总分和满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 穴位按摩联合中医特色护理模式能有效改善脓毒症患者睡眠质量和胃肠功能, 提高患者舒适度。)